2001
DOI: 10.1046/j.1083-4389.2001.00046.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Environmental Stress‐Regulated Genes in Helicobacter pylori by a lacZ Reporter Gene Fusion System

Abstract: This is the first time that a genomic transcriptional lacZ reporter gene H. pylori library has been used as a tool for the fast and efficient identification of environmental stress-regulated H. pylori genes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
39
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 52 publications
4
39
0
Order By: Relevance
“…To confirm that similar amounts of total RNA were used in the individual reactions, RT-PCR with primers based on the housekeeping gene katA, encoding the catalase enzyme (28), was carried out in parallel. It was previously demonstrated that the katA gene is constitutively transcribed under the growth conditions used in the present study (11) and was therefore considered to be a valid control for RT-PCR. To exclude the presence of residual DNA, for each RNA sample the complete RT-PCR procedure was also carried out without adding RT.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To confirm that similar amounts of total RNA were used in the individual reactions, RT-PCR with primers based on the housekeeping gene katA, encoding the catalase enzyme (28), was carried out in parallel. It was previously demonstrated that the katA gene is constitutively transcribed under the growth conditions used in the present study (11) and was therefore considered to be a valid control for RT-PCR. To exclude the presence of residual DNA, for each RNA sample the complete RT-PCR procedure was also carried out without adding RT.…”
Section: Methodsmentioning
confidence: 99%
“…Fragments of 644 to 1094 bp, containing the 5Ј end of the upstream gene (homolog of HP1406 [37] and JHP1298 [2]), the promoter region, and the 5Ј end of the res gene, were amplified by PCR using primers with a 5Ј extension containing a BamHI restriction site (Table 1). PCR fragments were cloned in the pGEM-T easy vector (Promega) and, as described previously (11), subcloned into the unique BglII site upstream of the promoterless lacZ reporter gene in the pBW vector, resulting in the suicide plasmids pRES284, pRES60, and pRES29. These plasmids were transformed into H. pylori strain 1061, and subsequent selection on kanamycin-containing agar plates resulted in the H. pylori recombinant clones RES284, RES60, and RES29, with a genomic pBW vector insertion flanked by two copies of the cloned fragment (see Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Expression of a number of other proteins has also been shown to be regulated by iron. Among these, several outer membrane proteins (29,31,73), the vacuolating cytotoxin (vacA) (61), the riboflavin biosynthetic genes ribAB (72), and the fumarate reductase genes frdCAB have all been shown to exhibit changes in expression in response to varying concentrations of iron (20). Increased expression of the vacA toxin is in keeping with the finding that in addition to regulating genes that are important for iron uptake and homeostasis, many pathogenic organisms regulate virulence factors in response to iron concentration (9).…”
mentioning
confidence: 99%
“…These insertions are predicted to disrupt the encoded proteins at amino acids 404 (FlaA), 342 (HP0609), and 167 (HP0689). Introduction of the transcriptional reporters into the H. pylori chromosome was accomplished by natural transformation and allelic exchange as previously described (9,12). Transformants were initially selected on the basis of antibiotic resistance, and insertion of reporters into the desired sites was confirmed by PCR analyses of genomic DNA.…”
mentioning
confidence: 99%